CONCEPTUALIZATION OF HAPPINESS ACROSS CULTURES AND ROLE OF RELIGION: A THEMATIC ANALYSIS ON YOUNG ADULTS - Javaid, Zartashia Kynat; Faizi, Dr. Waqar-un-Nisa; Lodhi, Atif Khan; Kamran, Muhammad (Journal of Arts & Social Sciences, 2024)
All of us experience happiness, but the ways we pursue and perceive it are different. Happiness is a significant component of our lives; we are all striving for it. In this study, we examined how cultural perspectives affect our happiness. Cultural perspectives play an important role in shaping our perception of happiness and in achieving it. We used qualitative research design, and conducted semi-structured interviews for data collection. We included 15 participants by using cluster sampling technique. All participants were university students; they were from different cultures of Pakistan (Punjabi, Pashtoon, Saraiki, Gilgiti and Baloch). For data analyzing, we used thematic analysis. Through thematic analysis, following themes were emerged; the conception of happiness across different cultures of Pakistan, how culture brings happiness among its people, the negative effects of culture on happiness, the impact of modernization and globalization, the impact of socioeconomic status, and ways to promote happiness. The findings of this research on cultural perspectives of happiness among university students have various implications for policymakers, education, and professionals of mental health. This study helps in understanding the complex relationship of culture, religion, and happiness. It can also be useful in enhancing wellbeing in diverse cultural context.